Studies on the Biology of Leaf Roller, Ancylis sativa (Liu) (Lepidoptera: Tortricidae) a Major Pest of Jujube (Ziziphus mauritiana) - Imtiaz A.Nizamani,; M.Ibrahim Khaskheli,; Aslam Bukero,; Niaz A. Wahocho,; Shafique A. Nizamani ,; Naeem A. Qureshi, (Journal of Basic & Applied Sciences, 2016)
Jujube, Ziziphus mauritiana Lam.is one of the most important fruit crops of Sindh, Pakistan, and isconsumed due to good flavour and high nutritional value. However, the occurrence of Jujube leaf roller Ancylis sativa (Liu) is a major threat to reduce the production of fruits, ultimately causing tremendous economic loss to the growers. The present study is the first comprehensive attempt on biology of Jujube leaf roller. There were five larval stages between egg and pupa. Adults were usually tan or brown, have mottled areas or dark bands. Average size of adult measured 9.53 mm long and 2.85 mm wide, wing span ranging from 16 to19 mm.